2019
DOI: 10.1037/fam0000520
|View full text |Cite
|
Sign up to set email alerts
|

Behind bars but connected to family: Evidence for the benefits of family contact during incarceration.

Abstract: Incarceration separates individuals from their families and communities, strictly limiting and controlling contact with the outside world. Despite these barriers, those who maintain contact with their families during incarceration tend to function more adaptively postrelease. Within a longitudinal framework, the current study examines mechanisms (i.e., family connectedness, postrelease planning) by which contact with family during incarceration may impact postrelease functioning (i.e., recidivism, substance mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
(67 reference statements)
1
26
0
Order By: Relevance
“…Contact between inmates and family members can occur through in-person visits, mail, and telephone calls. These traditional methods of communication have been found to be largely associated with a range of positive outcomes including less inmate misconduct (Cochran, 2012;Pierce et al, 2018), lower risk of recidivism (Duwe & Clark, 2013), successful postrelease employment, lower levels of substance use (Visher et al, 2013), improved mental health during the transition into the community (Folk et al, 2019), and in the case of conjugal visits, lower risk of in-prison sexual offending (Dalessio et al, 2013). A summary of research found that child contact while in prison had a positive effect on incarcerated individuals, especially within settings that included supportive interventions (Poehlmann et al, 2010).…”
Section: Contact Between Children and Fathersmentioning
confidence: 99%
“…Contact between inmates and family members can occur through in-person visits, mail, and telephone calls. These traditional methods of communication have been found to be largely associated with a range of positive outcomes including less inmate misconduct (Cochran, 2012;Pierce et al, 2018), lower risk of recidivism (Duwe & Clark, 2013), successful postrelease employment, lower levels of substance use (Visher et al, 2013), improved mental health during the transition into the community (Folk et al, 2019), and in the case of conjugal visits, lower risk of in-prison sexual offending (Dalessio et al, 2013). A summary of research found that child contact while in prison had a positive effect on incarcerated individuals, especially within settings that included supportive interventions (Poehlmann et al, 2010).…”
Section: Contact Between Children and Fathersmentioning
confidence: 99%
“…Studies among justice-involved individuals show that social support is linked to better mental health and adjustment, buffering the impact of depression on substance use (Mowen, Boman IV, & Schweitzer, 2020 ) and exposure to stressors on engagement in violent/criminal behavior (Maschi, 2006 ; Robbers, 2004 ). Support during incarceration in particular (e.g., visitation, phone calls) is linked to better connectedness with family and better mental health (Folk, Stuewig, Mashek, Tangney, & Grossmann, 2019 ). Lack of perceived social support may be a risk factor that exacerbates the association between stressful life events and poor well-being among incarcerated individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Others admitted they believed their children were better off without them. These anxieties can stifle the potential for bonding with children during periods of separation and further dilute the presence of fathers in the lives of their children and their role as effective parents (Folk et al, 2019).…”
Section: The Role Of Pat In Mending Encouraging and Enhancing Relationships Between Children And Their Incarcerated Fathersmentioning
confidence: 99%